Philosophy of Education: Pragmatism-Instrumentalism Concept of Forming the Future Human in Higher Education - Galina Beregova (International Society of Philosophy and Cosmology, 2016)
The paper discusses the possibility of forming new timeinduced planetarycosmic worldview attitudes of the man of the future by means of philosophy and through the system of higher education. It confirms a special mission of philosophy of education in forming the man of tomorrow and shows that it develops in the field of social philosophy and, making a comprehensive and interdisciplinary study of educational processes, ef ectively combines social science with pedagogy. The attention is focused on the fact that it is the philosophy of education that can target and fill the content of pedagogy with new knowledge, methods, techniques which, thanks to the latest teaching and educational approaches, will be implemented in the practice of forming the spiritual world of qualitatively new, modern generations. Based on a comprehensive approach to the educational process at universities, the study investigates the essence and mechanisms of a mindsetting function of philosophical knowledge that can provide successful training of responsible, creative, active young people to preserve the civilization on a planetarycosmic scale. It elaborates conceptual and methodological approaches to the formation of the world outlook of specialists by means of philosophy as the basis for the pragmatistinstrumentalist concept of philosophy of education, the essence of which is using philosophical knowledge as a tool of pragmatic ideological guidance on social and educational results: moulding the man of the future capable of ensuring the survival of civilization and humanity. The paper substantiates the content of philosophical knowledge in higher education which should naturally be consistent with the field and subject of study of future specialists since philosophical disciplines are still (at Ukrainian universities as well) often taught using outdated teaching practices: in a formal way without the necessary convergence of technical or natural sciences and humanitarian knowledge, humanization and humanitarization of higher education on the whole being the context and precondition of such convergence. Based on the analysis of the theory and practice of educational process in higher education, the article outlines the semantic content of philosophical knowledge that may include the philosophy of nature, anthropocosmism and philosophical energetics, as well as other components of philosophical knowledge, which significantly contribute to the development of axiological potential of the man of the future.